Selected letters of Sir J.G. Frazer - Frazer, James George, 1854-1941 (Oxford University Press, 2005)
This is a fully annotated edition of selected letters by (and in some cases to) Sir J.G. Frazer (1854-1941), the eminent anthropologist, classicist, and historian of religion. "Frazer" was read by virtually everyone working in those fields in the first third of the twentieth century. His great work, "The Golden Bough", offered a grand vision of humanity's mental and spiritual evolution - from vain attempts to compel the gods to do our bidding (which Frazer called magic) through equally vain attempts to propitiate the gods through prayer and sacrifice (his characterization of religion) to rationality and science. His richly varied correspondence with prominent figures such as Edmund Gosse, A.E. Housman, and Bronislaw Malinowski, among others, offers an unparalleled insight into British intellectual life of the time, and also throws light upon the composition of "The Golden Bough" itself.